The gut microbiome and sociability - Weber, Katherine T.; Varian, Bernard J.; Erdman, Susan E. (Frontiers in Neuroscience, 2024)
The human gut microbiome plays an important role in the maturation of the neural, immune, and endocrine systems. Research data from animal models shows that gut microbiota communicate with the host's brain in an elaborate network of signaling pathways, including the vagus nerve. Part of the microbiome's influence extends to the behavioral and social development of its host. As a social species, a human's ability to communicate with others is imperative to their survival and quality of life. Current research explores the gut microbiota's developmental influence as well as how these gut-brain pathways can be leveraged to alleviate the social symptoms associated with various neurodevelopmental and psychiatric diseases. One intriguing vein of research in animal models centers on probiotic treatment, which leads to downstream increased circulation of endogenous oxytocin, a neuropeptide hormone relevant to sociability. Further research may lead to therapeutic applications in humans, particularly in the early stages of their lives.